Traumatic brain injury and anger proneness: results from the Atherosclerosis Risk in Communities (ARIC) study - Law, Connor A.; Elser, Holly; Walter, Alexa E.; Mosley, Thomas H.; Walker, Keenan; Gottesman, Rebecca F.; Schneider, Andrea L. C. (Frontiers in Psychology, 2025)
Background/objectiveAssociations of traumatic brain injury (TBI) with subsequent increased anger proneness have been studied in younger populations, but less is known about potential bidirectional associations between TBI and anger proneness among older populations. This study aimed to investigate bidirectional associations between anger proneness and TBI among community-dwelling participants in the Atherosclerosis Risk in Communities Study.MethodsTBI was defined by self-report and ICD-9/10 codes. Anger proneness was defined using the Spielberger Trait Anger Scale. We performed 3 analyses: cross-sectional associations of prior TBI with anger proneness (Visit 2, 1990–1992, N = 13,694), associations of interval TBI with change in anger proneness (Visit 2, 1990–1992 to Visit 4, 1996–1998, N = 9,022), and prospective associations of baseline anger proneness with incident TBI (Visit 2, 1990–1992 to 12/31/2020, N = 11,713). Adjusted Tobit, linear, and Cox-proportional hazards regression models estimated associations, respectively.ResultsOverall, participants were a mean age of 57 years at Visit 2, 55% were female, and 24% were Black. In cross-sectional analyses, prior TBI was associated with slightly higher anger proneness (β = 0.35, 95% CI = 0.17, 0.54). In change analyses, interval TBI was not significantly associated with change in anger proneness score over time (β = 0.16, 95% CI = −0.16, 0.48). In prospective analyses, increasing baseline anger proneness was not significantly associated with incident TBI (moderate anger proneness: HR = 1.05, 95% CI = 0.95, 1.15; high anger proneness: HR = 1.15, 95% CI = 0.97, 1.37).ConclusionIn conclusion, this study did not find evidence for associations between TBI and anger proneness in this older population. Further research regarding relationships between anger proneness and TBI may not be warranted in older populations.